RANCANG BANGUN APLIKASI CHECK-IN DAN BILLING PADA APARTEMEN MARGONDA RESIDENCE V BERBASIS DEKSTOP - Rena Apriliany Putri; Ahmad Suryadi; Andi Dinullah (CV. Denasya Smart Publisher, 2024)
In the era of the development of science and technology as it is today, technology plays an important role to make an information need for many agencies and companies. Information technology itself is the most sought after and used by many agencies and companies to meet their business needs, not least in the lodging sector, which requires to provide accurate, fast, and easy information for employees and apartment guests. The purpose of this research is the formation of a check-in and billing application aimed at the Margonda Residence V Apartment in order to assist in its business processes, especially in the field of guest services at the Margonda Residence V Apartment.